A New Formalist approach to narrative Christology: Returning to the structure of the Synoptic Gospels - Dinkler, Michal Beth (HTS teologiese studies, 2017)
Today, scholars employ the label ‘narrative Christology’ with relative frequency, though they mean different things when they do so. In this article, I argue that to date, narrative Christology has not yet fully explored the parameters of what it means to attend closely to the narrative form of the Gospels’ presentations of Jesus. I propose, further, that recent developments in literary theory’s so-called ‘New Formalism’ offer useful tools and concepts for moving in that direction. The first part of the article briefly outlines previous scholarship, identifying similarities and differences between various approaches labelled ‘narrative Christology’. The second section introduces the major concepts of New Formalism and how they might extend narrative Christology’s capacity to take narrative form seriously as an object of analysis. The third section of the article offers a case study of a passage that appears in the triple tradition – the intercalated healing stories of Jairus’ daughter and the haemorrhaging woman in Mark 5.21–43; Luke 8.40–56; and Matthew 9.18–26 – in order to explore narrative structure on the micro-level. My ultimate goal is to show how New Formalism can contribute to a more robust narrative Christology and, in so doing, advance our understanding of the distinctive ways in which the Synoptic Gospels construct the figure of Jesus.